Inhibitory Effect of Evodiamine on Psoriasis Lesions and Itching in Mice - Liang J; Chen W; Zhou Y; Meng W; Xie M; Weng Y; Qin L; Li J; Wu G (Dove Medical Press, 2024)
Jianqiang Liang,1,* Weixiong Chen,2,* Yanhui Zhou,3 Weijia Meng,3 Man Xie,3 Yunying Weng,1 Luxuan Qin,1 Jianmin Li,4 Guanyi Wu1,5,6 1College of Basic Medicine, Guangxi University of Chinese Medicine, Nanning, People's Republic of China; 2School of Health Science and Engineering, University of Shanghai for Science and Technology, Shanghai, People's Republic of China; 3College of Pharmacology, Guangxi University of Chinese Medicine, Nanning, People's Republic of China; 4Department of Dermatology, The Third Affiliated Hospital, Guangxi Medical University, Nanning, People's Republic of China; 5Key Laboratory for Complementary and Alternative Medicine Experimental Animal Models of Guangxi, Nanning, People's Republic of China; 6Guangxi Key Laboratory of Translational Medicine for Treating High-Incidence Infectious Diseases with Integrative Medicine, Nanning, People's Republic of China*These authors contributed equally to this workCorrespondence: Guanyi Wu, School of Basic Medicine, Guangxi University of Chinese Medicine, 13 Wu He Road, Nanning, Guangxi, 530299, People's Republic of China, Email wugy@gxtcmu.edu.cnPurpose: This study seeks to investigate the effect of evodiamine on psoriasis and psoriatic pruritus.Methods: Imiquimod-induced psoriasiform dermatitis in mice was used as a model, and evodiamine was topically applied for seven days. The mice were observed daily for skin damage on the back, clinical score and their scratching behavior was recorded. Blood samples were collected on the final day of the experiment, and the serum levels of pruritus-associated inflammatory cytokines tumor necrosis factor (TNF) -α, interleukin (IL) − 23, and IL-17A were measured using enzyme-linked immunosorbent assay. Histopathological changes were observed in Hematoxylin and Eosin-stained skin specimens. The expression levels of transient receptor potential vanilloid (TRPV) 1, TRPV3, TRPV4, and the pruritus-related mediators Substance P (SP), nerve growth factor (NGF), and calcitonin gene-related peptide (CGRP) in the skin lesions were analyzed using Western blot and qRT-PCR. The effect of evodiamine on the exploratory behavior, motor, and coordination abilities of mice was assessed using open field, suspension, and Rota-Rod experiments. Molecular docking was utilized to verify the binding of evodiamine to the residues of TRPV1, TRPV3, and TRPV4.Results: Evodiamine reduced pruritus and inhibited inflammation by decreasing the levels of inflammatory mediators TNF-α, IL-23, and IL-17A in the serum of Imiquimod-induced mice and attenuated the mRNA and protein expression levels of SP, NGF, CGRP, TRPV1, TRPV3, and TRPV4 in the skin.Conclusion: Evodiamine is an effective treatment for psoriasis and pruritus, due to its ability to inhibit immune inflammation and pruritic mediators.Keywords: evodiamine, TRP channel, psoriasis